Design and Implementation of Taijiquan Learning System based on PHP+ MySQL - Li, Yang; Yuan, Ting; Yu, Kewei (2022 International Conference on Information System, Computing and Educational Technology (ICISCET), 2022)
As a traditional Chinese martial arts event, Tai Chi (Also known as Taijiquan) has a unique cultural connotation and excellent fitness function. MySQL is currently the most commonly used relational database. PHP is an open source dynamic web development script language. Researching a Tai Chi learning system based on PHP+ MySQL is of great help to the promotion of Tai Chi. Based on this, this article will study the subject of the design and implementation of the Taijiquan learning system based on PHP+ MySQL. This article first understands the students' understanding of "Twenty-Four Simplified Taijiquan" through questionnaires, and then analyzes the functional requirements of the system, and then designs the functional structure of the Taijiquan learning system. This article uses PHP+ MySQL software, three-dimensional technology, etc. to design the functional modules of Tai Chi. Finally, this article examines the effectiveness of the system in Taijiquan learning from the students' perspective and the students' satisfaction with the system. The survey results show that the highest user satisfaction is the content selection of the system, accounting for 88.21%, reflecting that Taijiquan is a familiar and favorite martial arts event with a broad mass base; followed by the speed of the system, accounting for 82.93%. It shows that the system reacts in time and runs smoothly.